Long Term Survivor of Vaginal Primary Malignant Melanoma (Journal of Armed Forces Medical College, Bangladesh, 2020)
Primary malignant melanoma of the vagina is a rare entity which constitutes less than 3% of vaginal cancer and only 0.3-0.8% of all melanomas in women. It has a high risk of local recurrence and distant metastasis. Once a recurrence is noted, survival is extremely poor. This article reports a case of primary vaginal melanoma with longer survival. As long-time survival of stage II vaginal melanoma is a rare phenomenon, this case is a unique one in Bangladesh; emphasizing on both importance of routine gynaecological examination for any suspicious pigmented lesions in the vagina as well as the necessity of further research on validating treatment protocols.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 114-115